Acute emergencies and critical care of the geriatric patient - Yoshikawa, Thomas T.; Norman, Dean C. (M. Dekker, 2000)
A review of the diagnosis and treatment of common surgical and medical emergencies in elderly patients. It examines drug therapies and drug prescribing protocols, identifies life-threatening drug reactions, weighs ethical issues, and addresses methods of profiling patients for nursing care.